2016
DOI: 10.7322/jhgd.119257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multidisciplinary program on autonomic modulation in overweight or obese children and adolescents

Abstract: Effects of a multidisciplinary program on autonomic modulation in overweight or obese children and adolescents J Hum Growth Dev. 2016; 26(2): 154-161 DOI: http://dx.doi.org/10.7322/jhgd.119257 AbstractPurpose: this study evaluated the effects of a multidisciplinary program on autonomic modulation in overweight or obese children and adolescents.Methods: fi fteen individuals with 10,93 ± 2,28 years were submitted to autonomic evaluation using heart rate variability before and after a program based on physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Recent literature has reported changes in autonomic activity within obese adolescents, demonstrating this as an important negative condition related to the increased risk of morbidity and mortality. 10,11 In this context, we investigated autonomic responses to exercise in both overweight and obese adolescents in order to determine differences in risk. To accomplish this, heart Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has reported changes in autonomic activity within obese adolescents, demonstrating this as an important negative condition related to the increased risk of morbidity and mortality. 10,11 In this context, we investigated autonomic responses to exercise in both overweight and obese adolescents in order to determine differences in risk. To accomplish this, heart Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…The studies’ flowchart and inclusion strategy are exemplified in Figure 1 . Amongst the 11 studies [ 3 , 5 , 6 , 17 , 21 , 41 , 42 , 43 , 44 , 45 ], a total of 398 individuals were included as a sample, comprising 176 boys and 222 girls aged 5 to 18 years, as illustrated in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The physical activity programs of the studies included in this review enforced many types of exercise. Other than aerobic training [ 3 , 5 , 6 , 21 , 41 , 42 , 43 , 44 ], the studies involved sports, commonly including soccer practice [ 45 , 46 ], and a solitary research study that assessed resistance training, conducted by Farinatti et al [ 17 ]. Notably, it was revealed that the training time—not only the session time but also the duration time in weeks—is foremost in maintaining the useful effect of exercise, as once the training periods ceased, the indices tended to slowly return to previous values [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have sought to describe the mechanisms of neuroendocrine regulation and it's influence on inflammatory diseases 4,8,10,[14][15][16] . The investigations are based on the effect of inflammatory cytokines on sympathetic activity and feedback cycles; existence of correlation between inflammation and HRV markers; an interaction of sympathetic predominance with inflammatory processes or even TNF itself as a direct depressant of HRV, causing an attenuation of beta adrenergic signaling 4,8,17 .…”
Section: Discussionmentioning
confidence: 99%